Habiba - Mohammed, Razinat T. (Book collections on Project MUSE., 2013)
It is believed that even silence will whisper when pushed to the wall. Saleh's love and respect for his mother, Hamsatu, is not only detrimental to his own life but also injurious to his family life. Hamsatu makes all the decisions in his life. She becomes despotic and decides who her son should marry and the type of children his wife should bear. Habiba is just thirteen when her grandmother, Hamsatu brings in a suitor, Zubairu, a contemporary of her late husband. Although Saleh wishes to send all his children to school, a rainstorm renders him hopeless as his mother takes ill and eventually dies.